Natural weathering performance of thermally treated poplar and black pine wood - Kamperidou, Vasiliki; Barboutis, Ioannis (Maderas. Ciencia y Tecnología, 2021)
Wood of poplar (Populus sp.) and black pine (Pinus nigra) species was subjected to thermal treatment under variant conditions of temperature, 180 ºC and 200 ºC, and duration of 3 h, 5 h, 7 h, and its resistance to natural weathering was investigated through the determination of crucial properties, such as the colour and surface roughness, while the appearance of the boards was assessed both visually and through a microscope, prior to and after their exposure outdoors. Prior to the outdoors exposure, it was observed that, as the intensity of heat treatment increases, wood tends to darken, with the parallel decrease of L* index, referring to tangential, radial and cross-sectional surface of both species specimens. The surface roughness of both wood species was found decreased only in the boards of the mildest treatment, while as the treatment intensity increases, the roughness degree demonstrated a strong increase compared to unmodified wood. After the 100-day exposure of poplar and pine boards to external conditions, they acquired a wilder look and new checks and cracks emerged in the boards surface, while fungi infestation signs appeared, most apparent in control and boards treated at milder treatments, with modified poplar boards to demonstrate more dense defects patterns on their surfaces, compared to modified black pine boards. A similar degree of discoloration recorded on unmodified boards was observed also on the thermally modified boards, which was except for the visual assessment, confirmed by the recorded progress of L*, a* and b* colour indexes of poplar and pine surfaces and is probably attributed to leaching of the water soluble extractives. The roughness of all of the exposed boards surfaces was found higher than the respective values recorded prior to the exposure and among the treated boards only those of the milder treatments presented lower roughness values than the unmodified ones. Thermal treatment enhanced the biological durability and dimensional stability of both species, but it did not adequately protect wood from the weathering effect when it was exposed outdoors. Nevertheless, wood modified at short-term heat treatments exhibited enhanced properties compared to unmodified wood and taking into account that the milder treatments did not cause mechanical strength loss, these materials could be utilized in applications where structures are not continually and directly exposed to aging factors, such as under shelter applications, or after the application of a thermal and surface modification with protective preservatives combination.